Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
[tex]\frac{x}{4} -\frac{ x+ 2 }{6} = \frac{x}{3} \ \ \cdot 12\\ \\3x-2(x+2)=4x\\ \\3x-2x-4=4x \\ \\3x-2x-4x=4 \\ \\-3x =4\ \ / :(-3)\\ \\x=-\frac{4}{3}\\ \\x=-1\frac{1}{3}[/tex]
[tex] \frac{x}{4} - \frac{x+2}{6} = \frac{1}{3} \ /\cdot12\\\\ \frac{x}{4}\cdot12 - \frac{x+2}{6}\cdot12 = \frac{1}{3}\cdot12\\\\3x-2(x+2)=4\\\\3x-2x-4=4\\\\x=8[/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.